Cross-cultural dialogue: Plato’s and Abu Bakr al-Razi’s discourse on the philosophic life - Moris, Megawati (2023)
The discourse on the philosophic life was said to be systematically and extensively started by the Greek philosopher Plato (d. 348/347 B.C.E). In the Islamic philosophical tradition, Abu Bakr al-Rāzī or Rhazes (d. 925 C.E) also showed concern about it in his writings. Both philosophers conceived the philosophic life as constituting the theoretical and practical dimensions. Knowledge is the fruit of the theoretical with reason or the intellect (al-‘aql) playing the primary role. As for the practical the focus is on the state of the human soul and ethics. In this presentation I will discuss Plato’s and al-Rāzī’s conceptions of the philosophic life based on philosophy’s meaning and objectives. In the discussion it will be made clear that the discourse of both philosophers—coming from very different traditions—on the subject are fundamentally and essentially the same. This is because philosophy as a discipline is concerned with answering the most fundamental as well as universal questions on reality and existence including that of human beings. Hence, philosophy ought to be considered as an important platform for cross-cultural dialogue among various and different members of societies and civilizations although today its role and significance are waning.